2002
DOI: 10.1067/mtc.2002.119695
|View full text |Cite
|
Sign up to set email alerts
|

The St Jude Medical symmetry aortic connector system for proximal vein graft anastomoses in coronary artery bypass grafting

Abstract: The aortic connector system was easy to handle and allowed quick creation of reliable, reproducible, and uniform anastomoses. In addition, anastomoses could be done without any clamping of the aorta, which is especially attractive for off-pump procedures, because aortic manipulation and therefore the risks of embolism and aortic dissection would be further minimized. In on-pump cases this technique would facilitate the single-clamp technique, again minimizing aortic manipulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
37
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(38 citation statements)
references
References 12 publications
1
37
0
Order By: Relevance
“…The flow waveforms were thus characterized by the peak Reynolds number of 5,495, mean Reynolds number of 1,054, and Womersley number of 17.8, based on the diameter of aorta. Based on in-vivo measurements [8], the mean flow rate of the graft was assumed to be 50 ml/min. The flow at the outlets of coronary artery and aorta were assumed to be fully developed with flow rate ratios of Q 4 /Q 1 = 1.04% and Q 2 / Q 1 = 98.96% within the cycle respectively.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…The flow waveforms were thus characterized by the peak Reynolds number of 5,495, mean Reynolds number of 1,054, and Womersley number of 17.8, based on the diameter of aorta. Based on in-vivo measurements [8], the mean flow rate of the graft was assumed to be 50 ml/min. The flow at the outlets of coronary artery and aorta were assumed to be fully developed with flow rate ratios of Q 4 /Q 1 = 1.04% and Q 2 / Q 1 = 98.96% within the cycle respectively.…”
Section: Boundary Conditionsmentioning
confidence: 99%
“…Despite initial promising reports, [15][16][17] several other case series have also reported early vein graft closures with the Symmetry device. [7][8][9][10][11][12] Cavendish et al reported a series of 121 CABG patients with Symmetry implants, of which 5 presented with an acute coronary syndrome 2 to 5 months after operation.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging reports have established safety of this device and overall patency rates appear to be equivalent to historic suture-mediated anastomosis control, although large randomized trials are lacking. Early bypass graft failures have been reported, with few patients requiring redo CABG [3,4]. We report cases of early ostial saphenous vein graft stenosis associated with the use of the Symmetry connector successfully revascularized by percutaneous intervention and stenting.…”
Section: Introductionmentioning
confidence: 94%